2014
DOI: 10.1038/nsmb.2822
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of starvation-induced assembly of the autophagy initiation complex

Abstract: Assembly of the preautophagosomal structure (PAS) is essential for autophagy initiation in yeast. Starvation-induced dephosphorylation of Atg13 is required for the formation of the Atg1-Atg13-Atg17-Atg29-Atg31 complex (Atg1 complex), a prerequisite for PAS assembly. However, molecular details underlying these events have not been established. Here we studied the interactions of yeast Atg13 with Atg1 and Atg17 by X-ray crystallography. Atg13 binds tandem microtubule interacting and transport domains in Atg1, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
266
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(279 citation statements)
references
References 40 publications
12
266
0
1
Order By: Relevance
“…16,36 More recently, an Atg17 binding region (17BR) of Atg13 was further mapped to residues 424 to 436 through a combination of crystallographic and biochemical methods. 23 Our CXMS data showed that the Atg13 [CTD] directly crosslinks to Atg17 in the context of the pentameric assembly. The Atg17-Atg13[CTD] interactions represented the most abundant intersubunit peptide group from our dataset ( Table S1).…”
Section: Interaction Between Atg17 and The Atg13[ctd]mentioning
confidence: 99%
See 4 more Smart Citations
“…16,36 More recently, an Atg17 binding region (17BR) of Atg13 was further mapped to residues 424 to 436 through a combination of crystallographic and biochemical methods. 23 Our CXMS data showed that the Atg13 [CTD] directly crosslinks to Atg17 in the context of the pentameric assembly. The Atg17-Atg13[CTD] interactions represented the most abundant intersubunit peptide group from our dataset ( Table S1).…”
Section: Interaction Between Atg17 and The Atg13[ctd]mentioning
confidence: 99%
“…Furthermore, recent phosphoproteomics analysis of S. cerevisiae Atg13 showed that these 3 serine residues are phosphorylated under nonstarvation conditions. 23 To determine the effects of phosphorylation on the interaction between Atg13 17BR2 and Atg17, we generated nonphosphorylatable ([3SA]) and phosphomimetic ([3SD]) mutations on Atg13 (residues 630 to 694) and analyzed these constructs by coprecipitation experiments. We found that while phosphomimetic mutation (3SD) did not affect the ability of Atg13 17BR2 to bind Atg17, the nonphosphorylatable mutation (3SA) significantly enhanced this interaction (Fig.…”
Section: Interaction Between Atg17 and The Atg13[ctd]mentioning
confidence: 99%
See 3 more Smart Citations